Narco-degradation: Cocaine trafficking's environmental impacts in Central America's protected areas. (August 2021) - Devine, Jennifer A.; Wrathall, David; Aguilar-González, Bernardo; Benessaiah, Karina; Tellman, Beth; Ghaffari, Zahra; Ponstingel, Daria
Highlights: Drug trafficking causes negative environmental impacts in Central American Protected Areas, what we call "narco-degradation." Drug trafficking enables and the proliferation of illicit markets trafficking people, flora, fauna, and antiquities. Types and scales of narco-degradation reflect the drug trafficking node's age, supply chain, and geographic attributes. Narco-degradation undermines livelihoods and governance, particularly for Indigenous peoples and peasants in rural and protected areas. Conservation and drug policies must be reformulated in tandem to protect Central America's forests and forest communities. Abstract: Central America exemplifies a dynamic unfolding around the world where transnational illicit economies are driving land use change. Despite an extensive network of protected areas, Central America has one of the highest deforestation rates in the world in the past 20 years. Some of this forest loss is due to the international cocaine trade, as drug trafficking organizations launder money into extractive economies and seek to control territories along their supply chain. While research documents land change from narcotrafficking in transit nodes, or narco-deforestation (e.g. Sesnie et al., 2017), less research exists examining other environmental impacts near cocaine transit nodes in protected areas and biodiversity hotspots, which we term "narco-degradation." We conducted i) interviews and participatory mapping exercises with 65 actors working in protected areas in Guatemala, Honduras and Costa Rica and ii) 11 workshops with 76 protected areas managers to understand and document spatial concentration of different types of narco-degradation. Coded interviews and maps yield 500 narco-degradation activities occurring between 2000 and 2018. Our analysis reveals that narco-trafficking affects multiple ecosystems, not only forests, and that variations in narco-degradation types and intensities reflect differences in the three nodes' transportation practices (air, land, maritime), their age and activity levels (emerging nodes, hotspots, and declining nodes), and their physical geography. In all three protected areas, narco-trafficking accelerates the conversion of natural resources into commodities (such as land, lumber, minerals, and fauna), their extraction, and entry into legal and illegal markets. We conclude by arguing that narco-degradation negatively and disproportionately impacts the livelihoods and governance structures of Indigenous and peasant communities living in and around Central America's protected areas. These insights contribute an integrated socio-ecological analysis of the role of narco-capital and cocaine trafficking's contribution to illicit global environmental change.